Conservation program for freshwater stingrays in the Musi River, Palembang City, South Sumatra: Stakeholders analysis and priority programs - Sahaya Aulia Azzahra; Pini Wijayanti; Nabila Nur Septiani; Lailatun Nikmah (Center for Science and Technology, IAIN Surakarta, 2024)
Through the Minister of Maritime Affairs and Fisheries Decree (Kepmen KP) 01/2021, the Indonesian Government has granted full protection status for three freshwater stingray species found in the Musi River, Palembang City, South Sumatra. However, enforcement of regulations related to the full protection of these three species remains suboptimal. Therefore, the active involvement of stakeholders and implementation of practical conservation strategies are essential. This research aims to identify the interactions among stakeholders involved in managing freshwater stingrays and to develop priority conservation programs for these species in the Musi River, Palembang City, South Sumatra. The findings emphasize the key stakeholders in management of freshwater stingrays, including the Palembang City Fisheries Office, Fisheries Extension Officers in Palembang City, under the Research Institute for Fisheries Research and Fisheries Extension Palembang institution (BRPPUPP), Fishery Resources Surveillance and Monitoring (PSDKP) Batam Palembang Work Area, Coastal and Marine Resources Management Agency (BPSPL) Padang Palembang Work Area, and fishermen. The proposed priority conservation programs for freshwater stingrays include public awareness campaigns to promote the importance of full protection for these species, research on the biological characteristics and habitats of freshwater stingrays, and enhanced surveillance achieving through intensive monitoring by Community Surveillance Groups (Pokmaswas) and by increasing the number of personnel and fisheries surveillance fleets. Collaborative program development among stakeholders is critical to ensure the success of the freshwater stingray conservation initiatives in the Musi River.